How to Snog a Hagfish! : Disgusting Things in the Sea - Eyers, Jonathan (Bloomsbury Pub., 2012)
For most people, seasickness is the most unpleasant thing they experience at sea. However, beneath the surface is a whole other world, and a lot of it could turn all but the strongest stomachs. When attacked, the hagfish (also known as the slime eel) ties itself in a knot that travels the length of its body, squeezing out mucus by the bucketful and making it impossible for a predator to keep hold. To eat, a starfish regurgitates its stomach, digests its food then swallows its stomach back down again. Pearlfish stick close to sea cucumbers, whose bowels they swim into when danger's near. And wi.